Increasing Public Knowledge about Stunting and Complementary Foods as an Effort to Prevent Stunting in Tanjungwangi Village Tanjungmedar District - Mona Yulianti; Dini Afriani; Puji Nurfauziatul Hasanah; Nuridha Fauziyah; Balkis Fitriani Faozi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Stunting is a nutrition problem which caused children’s growth and development disruption in Indonesia. Tanjungwangi Village is the priority locus of stunting for 2021 in Tanjungmedar District with incidence rate reached 28.57%. The implementation of this community service aimed to increase public knowledge about stunting and the fulfilment of nutritious complementary foods as an effort to prevent stunting. This community service activity was carried out in September 2021. The focus of this community service activity was to increase public awareness about stunting and its prevention efforts through the fulfilment of nutritious Complementary foods. The community conducts a pre-test before providing counselling with the aim of knowing the description of community knowledge about stunting and Complementary feeding. Counselling is carried out offline, including counselling on stunting and stunting prevention efforts including the fulfilment of Complementary feeding for toddlers. The community returned to do post-tests after being given counselling with the aim of knowing the overview of community knowledge after being given counselling. The result is that after being given counselling, public knowledge about stunting and Complementary feeding has increased. This activity went good and the community was very enthusiastic about listening to the counselling.